2020
DOI: 10.1177/0379572120968978
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Stunting and Thinness/Wasting Among Schoolchildren of Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Background: Several studies have been carried out on assessing the prevalence of undernutrition and possible determinants among schoolchildren in Ethiopia, but there is a lack of systematically gathered and analyzed information. Objective: This systematic review and meta-analysis aimed to summarize epidemiological data on undernutrition and possible determinants among schoolchildren in Ethiopia. Methods: We conducted a systematic review using open access articles that report the prevalence of stunting and wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 58 publications
5
25
3
Order By: Relevance
“…The zinc density in the optimized formulation was 0.4 mg/100 kcal (Table 4) and thus below the recommended value of 1.6 mg/100 kcal for 6‐ to 8‐month‐old infants. The Ca, Fe, and Zn contents of the individual flours used in the current formulation were in agreement with those reported in the literature, in particular for kocho (Abebe et al., 2007; Andeta et al., 2019; Atlabachew & Chandravanshi, 2008; Hailegebriel, 2020). To meet the daily requirements for Na, Mg, P, and K for infants and young children, it would be necessary to feed the optimized formulation two to three times per day.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The zinc density in the optimized formulation was 0.4 mg/100 kcal (Table 4) and thus below the recommended value of 1.6 mg/100 kcal for 6‐ to 8‐month‐old infants. The Ca, Fe, and Zn contents of the individual flours used in the current formulation were in agreement with those reported in the literature, in particular for kocho (Abebe et al., 2007; Andeta et al., 2019; Atlabachew & Chandravanshi, 2008; Hailegebriel, 2020). To meet the daily requirements for Na, Mg, P, and K for infants and young children, it would be necessary to feed the optimized formulation two to three times per day.…”
Section: Discussionsupporting
confidence: 90%
“…In low‐income countries, inadequate nutrient intake from suboptimal complementary feeding in combination with a high incidence of infections at an early age is the major cause of high stunting rates and impaired development (Masuke et al., 2021). Most rural households in these countries do not have access to animal protein or fortified foods (Hailegebriel, 2020). Consequently, many resource‐poor families rely on plant‐based diets for their infants, which are usually based on a single type of cereal grain but prepared through different methods of cooking.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that the odds of stunting are higher among children whose mothers can read and write compared to those mothers who attend secondary school and above. This is supported by the studies conducted in different parts of the world [ 12 29 33 34 35 ]. This could be explained by the fact that women with a higher education, owing to their exposure to the outside world, are more aware of personal hygiene and of promotive and curative health care than uneducated or less-educated women.…”
Section: Discussionmentioning
confidence: 52%
“…The main outcome variable was stunting (yes/no), reflecting failure to receive adequate nutrition over a long period, resulting in low height-for-age at < –2SD of median value of the National Center for Health Statistics (NCHS)/WHO international growth reference [ 35 ]. The independent variables were sociodemographic characteristics of the child (age, sex); sociodemographic characteristics of the caretaker/mother head of household; mother’s age, education, background, monthly income; mother’s occupation; environmental and hygiene related factors (type of house, type of water source, toilet availability); health service utilization (history of mother related to number of children, antenatal care (ANC) follow up, family planning (FP) use, place of delivery, immunization, deworming); nutrition-related characteristics (dietary history of children/caregiver, exclusive breastfeeding (EBF), time of complementary feeding start, duration of breastfeeding); and health care characteristics (infection).…”
Section: Methodsmentioning
confidence: 99%
“…The problem of undernutrition is a global concern in recent years and it is increasing at a wider rate in developing countries like India [ 1 ]. The main reason for focusing the analysis on undernutrition is that undernutrition continues as an economic ’macro’ issue related to food entitlements, poverty, and the socio-economic structure of societies as well as a primary cause of disease susceptibility, morbidity and mortality throughout the Third World [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%